2003
DOI: 10.1063/1.1632029
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of ZnO/GaN heterostructure and its near-ultraviolet light-emitting diode

Abstract: We report on photoluminescence in a ZnO/GaN heterostructure, which showed a donor–acceptor pair emission band at 3.270 eV and the longitudinal optical phonon replicas at 12 K. In comparison with p-type GaN, the positions of the peaks are redshifted. This may be associated with the variation of the residual strain in the GaN layer of the heterostructure. Using this heterostructure, near-ultraviolet light-emitting diodes were fabricated and their electroluminescence properties were characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(45 citation statements)
references
References 16 publications
1
44
0
Order By: Relevance
“…[4][5][6][7] An alternative approach is to fabricate heterojunction devices by using other available p-type materials, such as p-GaN, p-Si, p-NiO, p-type organics etc. [8][9][10][11][12][13][14][15] Among them, GaN has been considered as the most suitable one because of its similar energy band structure and small lattice mismatch with ZnO. However, the staggered band alignment (type II) of the n-ZnO/p-GaN heterojunction inevitably causes an energy barrier at the heterointerface, resulting in low injected carriers that can cross the junction for electron-hole recombination and degrading the performance of the device.…”
mentioning
confidence: 99%
“…[4][5][6][7] An alternative approach is to fabricate heterojunction devices by using other available p-type materials, such as p-GaN, p-Si, p-NiO, p-type organics etc. [8][9][10][11][12][13][14][15] Among them, GaN has been considered as the most suitable one because of its similar energy band structure and small lattice mismatch with ZnO. However, the staggered band alignment (type II) of the n-ZnO/p-GaN heterojunction inevitably causes an energy barrier at the heterointerface, resulting in low injected carriers that can cross the junction for electron-hole recombination and degrading the performance of the device.…”
mentioning
confidence: 99%
“…It is one of the promising candidates for high-stability, room-temperature luminescent and laser devices. [1,2] A number of studies have been reported on the development of optoelectronic devices using ZnO thin films, [3] ZnO nanowires, [4][5][6][7] or ZnO nanoparticles. [8] However, the growth of ZnO usually contains oxygen vacancies, which makes ZnO intrinsically n-type in nature with defect emission.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, it has been extensive studied both theoretically and experimentally in the past decades and has often been used in designing electronic devices to enhance the device performance. There are many different ways to apply strain, e.g., by applying external stress, having lattice and/or crystal structure mismatch between the epi-film and substrate [4] or between the layers in a heterostructure superlattice [7], or having reconstructions on a polar surface [8].…”
Section: Unusual Nonlinear Strain Dependence Of Valance-band Splittinmentioning
confidence: 99%